Factors affecting bank risk taking: Evidence from Japan - Konishi, Masaru; Yasuda, Yukihiro (Journal of Banking & Finance, 2004)
Using recent data from Japan, this paper examines empirically the determinants of risk taking at commercial banks. We find that the implementation of the capital adequacy requirement reduced risk taking at commercial banks. The acceptance of retired government officials on banks’ boards has an insignificant effect on bank risk. The relationship between the stable shareholders’ ownership and bank risk is nonlinear; the risk decreases initially with the ownership by stable shareholders, and then increases as the asset substitution effect dominates the effect of managerial entrenchment on bank risk. The decline of franchise value increases bank risk.